Peningkatan Komunikasi Ilmiah Siswa SMA melalui Model Quantum learning One Day One Question Berbasis Daily Life Science Question - Majdi, Muhammad Kamal; Subali, Bambang; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2018)
This study aims at determining the effect of applying One Day One Question Quantum learning Model Based On Daily Life Science Question on the ability of students’ scientific communication skill and its enormous improvement. The method used was true experimental design with pretest-posttest control group design. Samples were taken by simple random sampling technique in SMA Negeri 13 Semarang with X-MIPA 4 as experimental class and X-MIPA 1 as control class. This research was conducted by giving assignment to write some simple essays periodically with eight assessment indicators, i.e. source variation, source quality, relevance, writing quality, visual representation, title effectiveness, bibliography arrangement, and term and linguistic. The amount of improvement of students' scientific communication skills at the control class is 0.13 while the experimental class is 0.31. It can be concluded that the application of One Day One Question Quantum learning Model Based On Daily Life Science Question can improve students’ ability of written scientific communication.